Probability of mycotoxin contamination during post harvest operations of boro paddy (Journal of the Bangladesh Agricultural University, 2017)
John Deere and Frugal Moisture meter were compared with that of Indosaw standard. Frugal moisture meter was similar to the Indosaw standard but John Deere moisture meter were, on average, 2% higher than the standard. It is believed the John Deere model can be recalibrated to provide accurate results. Baseline survey on mycotoxins among 200 households of two districts of Bangladesh through the questionnaire indicate that the farmers were familiar with grain discoloration due to mold contamination but they did not have any idea about mycotoxins production on grains. Grain samples, one kg from each of 200 households were collected during May and June (Boro 2015), 119 had moisture content >14% and 37 had moisture content >20%. Purity, discoloration, mold invasion, insects and germination were assessed in the laboratory. Inert matter was 10% in 142 samples and >15% in 15 samples. Molds were associated with grain discoloration. Samples with high moisture content had higher quantity of moldy grains and stored pests. There was 25% grain discoloration of which 18% were moldy when the moisture content was >20%. Blotter incubation test revealed 19% incidence of Aspergillus growth on the 19% of the grains and Fusarium growth in 9% of the grains and produce Aflatoxins produced by Aspergillis and fumonisins by Fusarium were detected in rough rice of India (Reddy et al., 1986). Detection and quantification has of these two mycotoxins have not yet been done in Bangladesh. Through the present study the paddy samples will be analyzed by USDA Romer Lab test kit strips to create a national database on mycotoxins in paddy of Bangladesh.J. Bangladesh Agril. Univ. 14(2): 135-140, December 2016